2021 Asian Pacific Society of Cardiology Consensus Recommendations on the Use of P2Y12 Receptor Antagonists in the Asia-Pacific Region: Special Populations - Jack Wei Chieh Tan (Radcliffe Medical Media, 2021)
Advanced age, diabetes, and chronic kidney disease not only increase the risk for ischaemic events in chronic coronary syndromes (CCS) but also confer a high bleeding risk during antiplatelet therapy. These special populations may warrant modification of therapy, especially among Asians, who have displayed characteristics that are clinically distinct from Western patients. Previous guidance has been provided regarding the classification of high-risk CCS and the use of newer-generation P2Y12 inhibitors (i.e. ticagrelor and prasugrel) after acute coronary syndromes (ACS) in Asia. The authors summarise evidence on the use of these P2Y12 inhibitors during the transition from ACS to CCS and among special populations. Specifically, they present recommendations on the roles of standard dual antiplatelet therapy, shortened dual antiplatelet therapy and single antiplatelet therapy among patients with coronary artery disease, who are either transitioning from ACS to CCS; elderly; or with chronic kidney disease, diabetes, multivessel coronary artery disease and bleeding events during therapy.